The memoirs of Ambassador Henry F. Grady from the Great War to the Cold War - Grady, Henry Francis, 1882-1957 (University of Missouri Press, 2009)
"Ambassador Henry F. Grady's memoir describes his role in the evolving U.S. International economic policy during WW II and the Cold War. Serving key diplomatic posts in Italy, Greece, India, and Iran, Grady describes economic warfare during WW II, developing reciprocal trade agreements, and implementing the Truman Doctrine"--Provided by publisher.